Characteristic Of Green Technology For Sustainable Residential Project - Daud, Nur Adilah Mohamed (2018)
Receptivity of green technology for sustainable residential trend featured nowadays. Various advantages can be achieved if it starts from the beginning to implement green technology and sustainability starting from the home ownership. Commencement of business from developed countries such as Japan and the United States and most developing countries now participate strides to implement green technology and sustainability in every aspect. Green technology and sustainability is no stranger in the construction industry in Malaysia. However, many efforts should be intensified so that the implementation of green technology for the sustainable residential project can be accepted by the public. This is because the power to buy and own a home with green technology and sustainability concepts is in the hands of the buyer or the public. Continued efforts ensure that residential green technology and sustainable meet the characteristics favoured by the public, this study on characteristics of green technology and sustainability receptive to public for residential infrastructure in Malaysia. At the same time, it ensures that all parties involved in the construction industry whether from the relevant authorities, government agencies, private organizations and developers can play a key role in providing the best for the community, the nation and the future.